Folic Acid–Functionalized Metal-Organic Framework Nanoparticles as Drug Carriers Improved Bufalin Antitumor Activity Against Breast Cancer - Zeng, Hairong; Xia, Chao; Zhao, Bei; Zhu, Mengmeng; Zhang, HaoYue; Zhang, Die; Rui, Xin; Li, Huili; Yuan, Yi (Frontiers in Pharmacology, 2022)
Bufalin (Buf), an active ingredient of the traditional Chinese medicine Chansu, is known to have anticancer effects for breast cancer. However, its poor solubility, high toxicity, and extensive side effects limit its use. Metal-organic frameworks (MOFs) are a class of promising drug delivery systems known for their high porosity. Here, we designed and constructed pH-sensitive and redox-responsive folic acid–modified MOFs as drug carriers of Buf (FA-MOF/Buf). Moreover, the anticancer activity of nanomedicines was also explored in vitro and in vivo. Compared to free Buf, the FA-MOF/Buf nanoparticles demonstrated improved water solubility and stability, higher intracellular uptake, and enhanced cytotoxicity in breast cancer cells in vitro. Furthermore, it displayed improved accumulation in the tumor site, enhanced anticancer activity, and reduced side effects in vivo. Our results demonstrated that FA-MOF could be developed as a potential delivery system for Buf to improve its antitumor activity for breast cancer treatment.